From Grammar-Centered to Communicative Materials: Rethinking Arabic Language Teaching Resources in Higher Education - Muh. Sabilar Rosyad; Faiq Ilham Rosyadi; Nurul Huda; Nurhapsari Pradnya Paramita; Mi Guangli (Institut Agama Islam Negeri Curup, 2026)
This study examines how Arabic teaching materials mediate the relationship between grammatical knowledge and communicative competence in higher education. It addresses three questions: (1) to what extent materials remain grammar-centered, (2) how communicative and hybrid orientations are represented, and (3) how grammar can support effective communication. The study is urgent due to the persistent mismatch between communicative policy frameworks (e.g., CEFR) and the continued dominance of form-focused materials, which constrains learners’ communicative ability. Using a systematic state-of-the-art review of Scopus-indexed studies (2020–2026), this research applies thematic-critical synthesis. Data validity is ensured through transparent selection criteria, triangulation of empirical and conceptual sources, and iterative coding. Findings show that grammar-centered materials still dominate, while communicative innovations remain largely additive. Crucially, effective Arabic communication requires not the elimination of grammar, but its integration as a functional resource within meaning-focused and task-based learning. Misalignment occurs when grammar is treated as an end rather than a means. This study contributes by reconceptualizing the grammar–communication relationship and by proposing a context-sensitive framework for the development of communicative Arabic materials in higher education.